Energy Subsidy Reform : Lessons and Implications. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
Energy subsidies have wide-ranging economic consequences. While aimed at protecting consumers, subsidies aggravate fiscal imbalances, crowd-out priority public spending, and depress private investment, including in the energy sector. Subsidies also distort resource allocation by encouraging excessive energy consumption, artificially promoting capital-intensive industries, reducing incentives for investment in renewable energy, and accelerating the depletion of natural resources. Most subsidy benefits are captured by higher-income households, reinforcing inequality. Even future generations are affected through the damaging effects of increased energy consumption on global warming. This paper provides: (i) the most comprehensive estimates of energy subsidies currently available for 176 countries; and (ii) an analysis of ?how to do energy subsidy reform, drawing on insights from 22 country case studies undertaken by IMF staff and analyses carried out by other institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet